DESCRIPTION OF THE MOST COMMON EXTREMOPHILIC BACILLI IN WATERS OF LAKE SEVAN BASIN (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
The diversity of extremophilic bacilli in waters of Lake Sevan basin was studied. On the base of morphological, cultural, physiological and biochemical properties the taxonomic position of the most common isolates was determined. It was shown that the microphlora of extremophilic bacilli was represented by species Bacillus subtilis, B. licheniformis, B. stearothermophilus and B. alcalophilus.
Keywords: waters of Lake Sevan basin; extremophilic bacilli; microphlora